2018
DOI: 10.1021/acs.analchem.8b00135
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Sample Preparation for Alpha Spectroscopy with Ultrafiltration Membranes

Abstract: This contribution describes a rapid, fieldable alpha spectroscopy sample preparation technique that minimizes consumables and decreases the nuclear forensics timeline. Functional ultrafiltration membranes are presented that selectively concentrate uranium directly from pH 6 groundwater and serve as the alpha spectroscopy substrate. Membranes were prepared by ultraviolet grafting of uranium-selective polymer chains from the membrane surface. Membranes were characterized by Fourier-transform infrared spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Duval et al developed a method to graft EGMP from polyethersulfone membranes for the isotopic screening of waterborne uranium. After filtering solutions spiked with 233 U, the modified membranes achieved 233 U peak resolutions ranging from 17 to 33 keV FWHM [12]. Furthermore, the peak resolutions achieved by the membranes were sharp enough to distinguish 238 U (4.198 MeV) from 234 U (4.775 MeV) after filtering a spiked groundwater source at pH 6.…”
Section: Introductionmentioning
confidence: 98%
“…Duval et al developed a method to graft EGMP from polyethersulfone membranes for the isotopic screening of waterborne uranium. After filtering solutions spiked with 233 U, the modified membranes achieved 233 U peak resolutions ranging from 17 to 33 keV FWHM [12]. Furthermore, the peak resolutions achieved by the membranes were sharp enough to distinguish 238 U (4.198 MeV) from 234 U (4.775 MeV) after filtering a spiked groundwater source at pH 6.…”
Section: Introductionmentioning
confidence: 98%
“…Beyond their use for separations, the sorbents can be integrated with sensing platforms. For example, membranes designed to bind uranium accelerated the preparation of samples for nuclear forensic analysis by alpha spectroscopy . Additionally, sorbents functionalized with terpyridine moieties captured heavy metal ions with high affinity (Figure C) and simultaneously served as fluorescent probes that quantified the extent of sorbent saturation …”
Section: Introductionmentioning
confidence: 99%
“…For example, membranes designed to bind uranium accelerated the preparation of samples for nuclear forensic analysis by alpha spectroscopy. 68 Additionally, sorbents functionalized with terpyridine moieties captured heavy metal ions with high affinity (Figure 1C) and simultaneously served as fluorescent probes that quantified the extent of sorbent saturation. 69 While the primary function of a membrane is to mediate transport, membrane reactors 70 that transform solutes as they permeate 71 can be realized by immobilizing catalysts along the pore walls.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, functionalized polymer films and thin-film composite membranes have been demonstrated for the extraction and screening of various radioisotopes in water. Combined with alpha spectrometry, these substrates greatly reduce the time involved for isotopic screening by combining purification, concentration, and sample mounting steps. Approaches to developing the functionalized polymer thin films fall into two general categories, the first being physical immobilization or encapsulation of extractive ligands into a polymer matrix, akin to how an extractive chromatography resin is formed.…”
mentioning
confidence: 99%
“…fwhm values for the alpha spectra of the Pu loaded on the grafted membranes were 28− 35 keV and were comparable to sources evaporated onto planchettes; however, significant tail contributions occurred in the grafted membranes due to Pu ions bound within the 1−1.5 μm thick samples. Duval et al 12 developed a UV-grafting method to modify PES ultrafiltration membranes with an extractive layer comprised of ethylene glycol methacrylate phosphate for capturing of uranium from groundwater. Using a 50 mL ultrafiltration cell, solutions spiked with 233 U were passed through the modified membranes, and the resulting uranium recoveries ranged from 81 to 88% for both deionized and simulated groundwater samples.…”
mentioning
confidence: 99%